Where are the children? - Clark, Mary Higgins (New York : Pocket, 1992)
Nancy had fled from the tragedy of her first marriage, the deaths of her two little children, and the charges against her. Now the safety of her new family is threatened when her son and daughter turn up missing.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Missing children -- Fiction; Mothers -- Fiction; Missing children -- Fiction; Mothers -- Fiction; Mystery fiction